Avaliação dos fatores preditivos dos pólipos endometriais em mulheres na pós-menopausa - Dias, Flávia Neves Bueloni [UNESP] (2014)
Objective: To evaluate the clinical predictive factors of endometrial polyps in postmenopausal women. Methods: In this clinical, analytical, comparative and cross-sectional study 132 patients with histopathologic diagnosis of endometrial polyp were compared with 264 without endometrial alterations (control), seeking healthcare at a Public University Hospital. In the study were included women with amenorrhea ≥ 12 months and age ≥ 45 years, in a proportion of 1 case to 2 controls. Clinical, anthropometric, laboratory and ultrasonographic data were collected for evaluating the predictive factors of endometrial polyps. For statistical analysis were used the Student-t, chi-square tests and logistic regression method (odds ratio-OR). Results: Patients with endometrial polyps were older and had more time since menopause when compared to control (P <.0001). A higher percentage of women with endometrial polyps were obese (72%) compared to control (39%) (P <.0001). The measurement of waist circumference was higher among patients with polyps (P = 0.0001). We observed a higher incidence of diabetes, hypertension and dyslipidemia in patients with endometrial polyps (P <.0001). According to the NCEP/ATP III, 48.5% of women with polyps and 33.3% in the control group were classified as having metabolic syndrome (P = 0.004). Analysis of risk for endometrial polyp formation was higher in patients with: BMI ≥ 25 kg/m2 (OR 4.66; CI 95% 2.16-10.05); glucose ≥ 100 mg/dl (OR 2.83; CI 95% 1.36-5.90); dyslipidemia (OR 7.02; CI 95% 3.70-13.32); diabetes (OR 2.58; CI 95% 1.05-6.32); and metabolic syndrome (OR 2.76; CI 95% 1.18-6.46). (P = 0.019) compared to control. Conclusion: In postmenopausal women, obesity, dyslipidemia, hyperglycemia and the presence of metabolic syndrome were predictive factors for endometrial polyp